2020
DOI: 10.3324/haematol.2020.261586
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress activates red cell adhesion to laminin in sickle cell disease

Abstract: Vaso-occlusive crises are the hallmark of sickle cell disease (SCD). They are believed to occur in two steps, starting with adhesion of deformable low-dense red blood cells (RBCs), or other blood cells such as neutrophils, to the wall of post-capillary venules, followed by trapping of the denser RBCs or leukocytes in the areas of adhesion because of reduced effective lumen-diameter. In SCD, RBCs are heterogeneous in terms of density, shape, deformability and surface proteins, which accounts for the differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…However, silencing Lnc NEAT1 in both HUVEC-Exos and H 2 O 2 -HUVEC-Exos did not affect the fluorescence signal intensity around the skin flap relative to that in HUVEC-Exos and H 2 O 2 -HUVEC-Exos, respectively. Previous study has showed that oxidative stress could activate the adhesion of RBCs to laminin by inducing post-translational modification of Lu/BCAM, which altered its distribution on the cell surface, resulting in aggregates with high binding potential to laminin [ 68 ]. Oxidative stress is one of the important pathogenesis of pancreatitis, leading to upregulation of adhesion molecules, which in turn accelerates disease progression [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, silencing Lnc NEAT1 in both HUVEC-Exos and H 2 O 2 -HUVEC-Exos did not affect the fluorescence signal intensity around the skin flap relative to that in HUVEC-Exos and H 2 O 2 -HUVEC-Exos, respectively. Previous study has showed that oxidative stress could activate the adhesion of RBCs to laminin by inducing post-translational modification of Lu/BCAM, which altered its distribution on the cell surface, resulting in aggregates with high binding potential to laminin [ 68 ]. Oxidative stress is one of the important pathogenesis of pancreatitis, leading to upregulation of adhesion molecules, which in turn accelerates disease progression [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…82,83 It is known that young low-density reticulocytes, released from the bone marrow due to hemolytic stress, adhere to LN in SCD primarily through a Lu/BCAM phosphorylation mediated mechanism, 84 not seen in highdensity mature sickle RBCs. 85 Likely, adherent RBCs in our assay are primarily reticulocytes, although sickle mature RBCs can also adhere on LN (previously reported to be 80% to 90% less than reticulocytes). 11 Altogether, these data suggest clinical relevance for the present assay in SCD, in which the OI measures the impact of stiff sickle RBCs on microvascular occlusion, and RBC adhesion measures the potential of sickle reticulocytes and mature RBCs to attach to exposed sub-endothelial-like matrices, as seen in microvascular damage (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, previously it has been shown that adhesion of reticulocytes to LN (isoform-10) is triggered by oxidative stresses through Lu/BCAM phosphorylation in reticulocytes but not in mature erythrocytes. 41 Nevertheless, given that reticulocytes spent much less time in circulation compared to the mature erythrocytes, the differences that we demonstrated between adhesion of mature erythrocytes and reticulocytes can be explained by the mechanisms that are relevant to the oxidative stress. Therefore, further comprehensive studies could be performed to elucidate the scale of the effects of SMase on sickle red blood cell adhesion.…”
Section: It Is Important To Note That Increase Of Mature Erythrocyte ...mentioning
confidence: 65%